Kearifan Lokal dan Konservasi Hutan: Studi Antropologi Ekologi tentang Relasi Manusia dan Lingkungan di Mandailing Natal, Sumatera Utara, Indonesia - Zulkifli Lubis; Saipul Bahri; Muhammad Bangun Siregar; Zoraya Alfathin Rangkuti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Forests have an important role in maintaining ecological balance, the sustainability of natural resources, and the social life of local communities. However, various pressures such as land conversion, exploitation of natural resources, and socio-economic changes have threatened the sustainability of forest areas in various regions of Indonesia, including Mandailing Natal Regency, North Sumatra. This research aims to analyze the role of local wisdom in forest conservation through an ecological anthropological perspective that emphasizes the reciprocal relationship between humans and the environment. The research uses a qualitative approach with ethnographic methods through participatory observation, in-depth interviews, focus group discussions, and documentation studies. The informants consist of traditional leaders, community leaders, forest managers, and communities living around forest areas. The data analysis was carried out thematically with the help of ATLAS.ti software. The results of the study show that the local wisdom of the Mandailing community functions as a social and cultural mechanism in regulating forest utilization, maintaining ecosystem balance, and forming collective awareness of the importance of environmental conservation. Indigenous values, prohibitions on the use of certain areas, and community-based natural resource management practices contribute to forest sustainability. This research confirms that the integration of local wisdom into conservation policies can strengthen sustainable and participatory environmental governance.